Study of the weighed metals in the abandoned tailing of Ticapampa - Romero, Alfonso (2012)
This study tell us about the presence of the heavy metals in the mining tailing of Ticapampa, which it is a mining solid waste, result of operations of treatment of metallurgy benefit by flotation, that is consider as an important environmental passive which produces an important negative impact such as: The Pollution of Environment of The river Santa. On the other hand, this study makes an geochemistry analysis of 14 points of sampling, between the most important are three points of sampling (P190, P192, P197), which are considered the most critical by geochemistry analysis because they contain major presence and amount of heavy metals.